A renewed territorial cohesion narrative. Reflections on the EU Territorial Agenda - Medeiros, E. (Informationen zur Raumentwicklung (IzR) / Information on spatial development, 2019)
This article debates the need for a renewed territorial cohesion narrative for an updated version of the EU Territorial Agenda. It proposes a more simplistic and practical vision for the territorial cohesion concept and the need to transform it into a measurable notion. It also advances alternative policy implementation avenues to achieve territorial cohesion policy goals at the national level. These include a policy investment focus on specific number of regional development hubs denominated “territorial cohesion cities” and the need for “territorial cohesion- related indicators